An overview of the challenges in Malaysian green construction / Asniza Hamimi Abdul Tharim ... [et al.] - Asniza Hamimi, Abdul Tharim; Aifa Syazwani, Zainudin; Noraidawati, Jaffar; Teh Zahariah, Nasaruddin; Muna Hanim, Abdul Samad (2015)
Green building means to refine and improve the design, construction and management practices so that building will last longer, cost less and contribute to healthy living. It also brings significant effects in protecting natural resources and improving the built environment. However, the green development approach often faces challenges and obstacles in terms of the implementation of the new procedures and technologies. The main objective of this paper is to explore the challenges encountered by the project manager in managing green building in Malaysia. Thus, this paper will also provide an overview on the Malaysian green assessment context thatis known as the Green Building Index (GBI). The Green Building Index (GBI) is an index on environmentally friendly building with the ability to save utility costs and preserve the quality of the external and internal environment. Therefore, it is crucial to identify the challenges in implementing the green building construction and management for the benefits of the building assessment. To achieve the main purpose of this paper, questionnaire surveys were conducted among project managers in the Klang Valley, Malaysia. Data obtained was then analyzed by using the SPSS software and the outcome fromthesurvey indicates eight main challenges in greenbuilding management in Malaysia faced by the project managers. Most of the respondent agreed that the most substantial challenge faced by the project manager in managing a green construction is the time factor. This result is similar to the findings from previous research which indicates that longer time is needed in pre-construction of the green construction projects.